A New Flexible Stress-Strength Model - Beiranvand, Alimohammad; Kazemi, Ramin; Kohansal, ‎Akram; Hormozinejad, Farshin‎ ‎ (Statistics, Optimization & Information Computing, 2021)
‎To introduce a flexible stress-strength model‎, ‎statistical inference of the stress-strength parameter R=P(X<Y)‎, ‎when stress X and strength Y are two independent‎ two-parametre new Weibull-Fr\’echet variables‎, ‎is considered under Type II progressive censored samples‎. ‎The MLE‎, ‎AMLE‎, ‎asymptotic confidence intervals‎, ‎Bayes estimate and HPD intervals of R are achieved in three different cases‎. ‎Also‎, ‎to compare the performance of three different methods‎, ‎we apply the Monte Carlo simulations and also analyze a data set for illustrative aims‎.